THE INFLUENCE OF COMPETENCE AND LEADERSHIP ON THE PERFORMANCE OF VILLAGE APPARATUS IN IMPROVING TOURISM DEVELOPMENT IN SEKAPUK VILLAGE, UJUNG PANGKAH SUB-DISTRICT, GRESIK REGENCY - Raharja, Wildan Taufik; Umiyati, Sri; Basyar, Muhammad Roisul; Nafi’ah, Binti Azizatun (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
In 2017, Sekapuk Village was an underdeveloped village with an IDM (Development Village Index) of 0.55%. Sekapuk Village has had a myriad of problems from time to time including poverty, a slum environment, flooding, and stagnant and undeveloped Village-Owner Enterprises. This study aims to test the hypothesis and identify the influence of competence and leadership on the performance of village apparatus in increasing tourism development in Sekapuk Village, Ujung Pangkah District, Gresik Regency. In this study using a quantitative research approach. Based on the results of the research that has been described in the discussion, it can be concluded that firstly, there is a significant influence between competence on the performance of village apparatus where the first hypothesis is accepted. That is, good competence is able to improve the performance of village apparatus in increasing tourism development in Sekapuk Village, Ujung Pangkah District, Gresik Regency. Second. Second, there is a significant influence of leadership on the performance of village apparatus where the second hypothesis is accepted. That is, the better the leadership that is applied, the performance of the village apparatus can be improved. Third, competence and leadership together have a significant effect on the performance of Sekapuk Village apparatus, Ujung Pangkah District, Gresik Regency where the third hypothesis is accepted